Intersemiotic Tropes as Genre Forming Factor - Yeremenko, Olena (Літературний процес: методологія, імена, тенденції, 2013)
The article probes into genre-forming function of intersemiotic tropes. A study of the collection of short stories “Singing Willow Tree Cradle: frescoes of occupation period” by Yevgen Gutsalo proves that poetic means from related arts pervade a form and content of a fictional text. Special attention is paid to cinematic imagery and fine arts techniques.